2016
DOI: 10.1590/0074-02760160238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environment, dietary regime and ageing on the dengue vector microbiota: evidence of a core microbiota throughout Aedes aegypti lifespan

Abstract: Mosquito midgut microbiota is a key component of vector competence, as gut bacteria can disturb pathogen development. In this study, we addressed the microbiota composition of Aedes aegypti during its lifespan, under field conditions. We also investigated the possible effects of environment, dietary regime and ageing on the gut community composition. We employed culture independent and dependent approaches to characterise vector microbiota. There was evidence of a lifelong stable core microbiota after mosquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
62
4
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 34 publications
11
62
4
2
Order By: Relevance
“…The overall uniqueness of the laboratory samples was also found to be pronounced in our samples contrary to other studies that find high degree of similarity between field and laboratory samples (Wang et al, 2011;David et al, 2016). We found all bacterial community compositions from each field location/season different from the laboratory samples via pairwise PERMANOVA (Figs 4, S6).…”
Section: Discussioncontrasting
confidence: 95%
“…The overall uniqueness of the laboratory samples was also found to be pronounced in our samples contrary to other studies that find high degree of similarity between field and laboratory samples (Wang et al, 2011;David et al, 2016). We found all bacterial community compositions from each field location/season different from the laboratory samples via pairwise PERMANOVA (Figs 4, S6).…”
Section: Discussioncontrasting
confidence: 95%
“…When abundant microbes were classified at higher taxonomic levels, our analysis found 22 families, with Enterobacteriaceae being the most common when disregarding Wolbachia. Bacteria found in mosquitoes were classified into five phyla with bacteria in the phylum Proteobacteria most prevalent in the microbiome, which is consistent with previous studies ( Osei-Poku et al, 2012 ; David et al, 2016 ; Muturi et al, 2016b ; Audsley et al, 2017a ), although other reports indicated Bacteroidetes or Acinetobacter phyla can be a major component of the microbiome ( Coon et al, 2014 , 2016b ; Minard et al, 2014 , 2015 ).…”
Section: Resultssupporting
confidence: 90%
“…albopictus at immature stages (larvae, pupae) while inhabiting water with different ampicillin concentrations but also the variations in the microbiome composition of unfed adult females hatched from the aforementioned pupae. The predominance of Proteobacteria in most immature stage groups was consistent with the findings of previous studies (Audsley et al, 2017; David, Santos, Vicente, & Maciel‐de‐Freitas, 2016; Muturi, Kim, Bara, Bach, & Siddappaji, 2016; Osei‐Poku et al, 2012). However, divergence was observed in the dominant phylum between adult females that were originating from immature stages in the ampicillin‐treated groups (A1–A4) and those originating from immature stages in the control group (A5) (Figure 1).…”
Section: Discussionsupporting
confidence: 90%